A implementação da meta 1 do Plano Nacional de Educação na educação infantil no município de Santa Maria/RS - Lemos, Carolina Oliveira (2018)
In the last decades, the debates about the universalization of preschool have intensified, which is considered a stage of Early Childhood Education and, currently, according to the legislation, is guaranteed as compulsory and free. In this context, the National Education Plan (Law n.13.005 / 2014) established as a goal (Goal 1) to universalize pre-school education in pre-school (4 and 5 years) until 2016 and reach 50% in nurseries (0 to 3 years). This goal is accompanied by strategies that include the necessary preparation and qualification of the teachers who work in this educational stage. Broadening the offer of positions is to legitimize a subjective right of the citizen, which is contained in the legal system of Brazil, as well as to effect the duty of the State to guarantee its offer. In line with the National Education Plan (2014-2024) is the goal 1 of the Municipal Education Plan, which includes in its text "Universalize, until 2016, Early Childhood Education in Pre-school for children from 4 to 5 years of age and increase the offer of Early Childhood Education in kindergartens for children up to 3 years old, in order to contribute to the achievement of the national goal (PNE 2014-2024) of 50% (fifty percent) by the end of the SME period and offering full-time public education for children with quality assurance in the care of children”. The general objective of this study is to know and analyze the process, strategies and weaknesses of the implementation of goal 1 in relation to the compulsory provision of preschool (4 and 5 years) in the National Education Plan in the Municipality of Santa Maria / LOL. The research is qualitative-quantitative, of the Case Study type, in which the instruments of data collection are the documentary analysis and semi-structured interview. The present study intends to discuss the policies implemented in the municipality of Santa Maria / RS to ensure the universalization of school attendance in the 4 and 5 year age group according to the PNE (2014-2024) and the PME (2015-2025). Finally, the final considerations refer to the most important points evidenced in the speech of the research participants and the data presented, the actions of the Municipal Education Department in relation to the attendance of preschool, the quality of Early Childhood Education and the view of the interviewees for the provision of quality public education. The present work is the result of the conclusion of the Professional Master's Course in Public Policies and Educational Management, through research line 1: Policies and Management of Basic and Higher Education. The final product is the diagnosis of the implementation of PNE Goal 1 in the municipality of Santa Maria / RS.